2014
DOI: 10.1155/2014/768186
|View full text |Cite
|
Sign up to set email alerts
|

The Smart Nonconserver: Preschoolers Detect Their Number Conservation Errors

Abstract: Classic developmental studies have established that children's number conservation is often biased by misleading intuitions. However, the precise nature of these conservation errors is not clear. A key question is whether children detect that their erroneous conservation judgment is unwarranted. The present study focuses on this critical error sensitivity issue. Preschool children were given a classic version of a number conservation task in which an intuitively cued response conflicted with the correct conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…or very hard ("Is Brussels a town in Suisse?"). The idea was that by presenting questions of varying difficulty we could quite naturally illustrate the response-confidence concept by pointing out that one might be sure about their response to some questions whereas one might be less sure about their response to other questions (e.g., De Neys, Lubin, & Houd e, 2014). For the hard questions, children were explicitly told by the experimenter that this was a really hard question and that they presumably felt unsure as to whether their answer was correct.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…or very hard ("Is Brussels a town in Suisse?"). The idea was that by presenting questions of varying difficulty we could quite naturally illustrate the response-confidence concept by pointing out that one might be sure about their response to some questions whereas one might be less sure about their response to other questions (e.g., De Neys, Lubin, & Houd e, 2014). For the hard questions, children were explicitly told by the experimenter that this was a really hard question and that they presumably felt unsure as to whether their answer was correct.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…The concern is that in lengthy test sessions with multiple items the repeated alteration of conflict and no-conflict control items might artificially direct participants to start monitoring for conflict which might result in an overestimation of the error sensitivity. To sidestep this potential complication, we have opted to limit the number of items (e.g., see also De Neys, Rossi, & Houd e, 2013;De Neys et al, 2014; for a related approach). In a developmental context this has the additional advantage that the study is kept short and children have little trouble staying maximally Fig.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…In general, children and adults prefer using fast heuristics spontaneously, but that choice does not indicate that they are illogical per se (Houdé, 2000) or that they are “happy fools” (De Neys et al, 2013, 2014). Psychologists had to be careful to avoid false negatives (Gelman, 1997), which is a strong tendency to say that those children or adults who fail a task are incompetent in the target domain of knowledge.…”
Section: From Piaget’s Theory To Inhibitory Control Modelmentioning
confidence: 99%
“…Given these findings, the presently established successful number conservation error detection at the preschool age might seem somewhat surprising at first sight. However, as noted by De Neys et al (2014), here one needs to take into account that even a less than fully functional ACC does not imply a lack of all conflict detection. Indeed, error monitoring studies have shown that even infants can detect errors in simple tasks that do not cue a strong intuitive response (Berger, Tzur, & Posner, 2006;Lubin et al, 2010;Lyons & Ghetti, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, such a study could adopt the task design of the behavioral conservation study of De Neys et al (2014) and also ask children to give confidence ratings in the scanner. This would allow us to directly link the confidence data to ACC brain activation, for example.…”
mentioning
confidence: 99%